Model Kepemimpinan Kepala Taman Kanak-Kanak pada Masyarakat Pandhalungan Kabupaten Jember - Reski Yulina Widiastuti; Aisyah Nur Atika; Laily Nur Aisiyah; Muhammad Haidlorh (PG-PAUD Trunojoyo, 2023)
Qualified kindergarten principals have different leadership models. Urban and rural areas with varying characters, cultural models, and speed of information influence the principal's leadership model in kindergarten. This study aims to determine the Leadership Model of Kindergarten Principals in the Pandahalungan community in urban and suburban Jember districts. Descriptive qualitative approach method combined with interview data collection techniques, observation, and documentation. Data analysis used partial interpretation, overall interpretation, and meaning. The research subjects involved in this study were principals and teachers of kindergarten institutions in urban and suburban areas. The results of applying the principal's leadership model, in kindergarten institutions in the Pandhalungan community in urban areas, principals use the transformational leadership model, and the suburban area leadership model mostly still uses the Transactional leadership model. Suggestions given by school principals to kindergarten institutions in the Pandhalungan community can take positive values in each leadership model adjusted to social, economic, cultural, and environmental factors.